The Cost of Caries in Primary Dentition: A Case Report of a Rare Cause - Vladimir Mitic; Sasa Cvetkovic (Clinical Case Reports)
ABSTRACT A 10.2‐year‐old girl, accompanied by her parents, came to the Department of Jaw Orthopedics at the Clinic for Dental Medicine. Based on the initial orthopantomography, multiple tooth impactions were diagnosed. In the upper jaw, the impaction of the canine and the second premolar on the left side was observed, along with.